Hypochlorite Detection by Fluorescent Sensors Bearing Long Alkyl Chains: The Role of Chain Length in Sensing Properties. Issue 11 (23rd November 2022) - Yang, Yuan; Li, Zhao; Dong, Fenghao; Lv, Jiawei; Han, Bingyang; Sun, Yuqing; Lu, Huiming; Lei, Ziqiang; Ma, Hengchang
Abstract: Three pyridinium derivatives bearing alkyl chains of different lengths (C1, C8, and C18) that show aggregation‐enhanced emission were synthesized. These compounds can be used to detect ClO − ion as the reaction releases the fluorescent core with an increase in emission intensity and change in absorption wavelength. The lowest detection limit of TPA‐Pyr‐18C was 6.04 μM. The length of the alkyl chain and resulting lipophilicity allowed the targeting of different subcellular structures. TPA‐Pyr‐18C could be used for staining yolk lipids in zebrafish. Abstract : The synthesis of three pyridinium derivatives with different alkyl chains is reported in this work. It was also shown that the response of TPA‐Pyr‐18 C to ClO − has a two‐channel response comprising absorption and fluorescence. The length of alkyl chain at the end of pyridinium salt could regulate the targeting of the probes to different subcellular structures. The probe molecule could effectively stain the lipid parts of zebrafish.